Le traduzioni in basso-tedesco medio del De regimine principum di Egidio Romano - Laura Gherardini (Filologia Germanica)
The so-called mirrors for princes (specula principum) are political and didactic writings which were primarily addressed to kings and lords and aimed at instructing them in the art of governance as well as teaching proper behaviour. They were widespread and appreciated during the Middle Ages. A very famous speculum is De regimine principum by the Augustinian friar Giles of Rome (1243-1316), who wrote this treatise for young Philip the Fair (1268-1314). His work was handed down in numerous manuscripts and was translated into several languages throughout Europe. In the German-speaking area six different translations are known, two of which are in Middle Low German: one attributed to Johannes von Brakel and preserved in a single paper manuscript, and another by an anonymous author, handed down in a parchment fragment and based on the version by Henri de Gauchi. Both manuscripts are dated around 1400. This paper compares the two translations: while the anonymous author manages to accurately translate the French text, probably in order to address a specific recipient, Johannes von Brakel is more independent from the Latin original; moreover, he addresses a wider audience. The different strategies they adopt could depend on the cultural and social milieus to which the diverse recipients belonged.